Diferenças e Desigualdades nas Creches da Zona Leste da Cidade de São Paulo : Um estudo comparativo das condições de trabalho e operação dos CEI diretos e CEI conveniados - Oliveira, Adriano Francisco ([Actas])
The present study conducted an analysis on policies for early children education in the city of Sao Paulo, establishing a comparison between the callled Direct Early Children Education Centers and the Contracted ones. Within this comparison, we find data extremely different on the two ways of managment listed above, regarding hours of teacher training, their rights and gains, the worked hours and amount of professionals involved in each of them. The results demonstrate that, although there are the same responsabilities in both situations, the rights concerning them are completely distinct